Preparation of Graphene by Oxidation-Reduction Method - Wang, Jing; Feng, Desheng; Cheng, Ran; Wang, Junping; Zou, Linchang; Zhang, Jin (Asian Journal of Chemistry, 2014)
Graphene nano sheets and graphene oxide were synthesized from natural flake graphite with Hummers and modified Hummers methods. By comparison the infrared spectrums of graphene, we found graphene oxide prepared by the modified Hummers method, in which a slight excess of concentrated sulfuric acid and excessive hydrogen peroxide was used to reduce the residual oxidant, could be reduced more completely and contains less oxygenated functional groups than Hummers method, showing that by controlling the experimental conditions and parameters of oxidation-reduction preparation process that we can reducted graphene oxide completely and get more perfect graphene crystal.